Association between Ureaplasma urealyticum colonization and bronchopulmonary dysplasia in preterm infants: a systematic review and meta-analysis - Chen, Xianhong; Huang, Xunbin; Zhou, Qiujing; Kang, Houxin; Qiu, Huixian; Shi, Lindong; Tang, Hong; Zeng, Shujuan (Frontiers in Pediatrics, 2024)
Background: Bronchopulmonary dysplasia (BPD) is the most prevalent chronic lung disease in preterm infants. Studies have shown that Ureaplasma urealyticum (UU) infection is linked to its pathogenesis. However, it remains controversial whether UU colonization in preterm infants increases the risk of developing BPD.Objective: This study aimed to conduct a systematic review and meta-analysis to summarize the correlation between UU and BPD.We searched PubMed, Embase, the Cochrane Library, Web of Science, Wanfang Database, Chinese National Knowledge Infrastructure Database, Chinese Science and Technique Journal Database, and the China Biology Medicine disc from their inception to March 15, 2024. We included cohort and case-control studies investigating the association between UU infections and BPD in preterm infants, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The Newcastle-Ottawa Scale was used for quality assessment. Outcomes were defined as the need for supplemental oxygen at 28 days (BPD28) and at 36 weeks postmenstrual age (BPD36). Considering the potential publication bias in observational studies, we used a random-effects meta-analysis model, assessed heterogeneity (I² ), performed subgroup analyses, evaluated publication bias, and graded the quality of evidence. Results: The meta-analysis included 36 cohort studies encompassing 5,991 participants. Among these, 20 reported on BPD28, 13 on BPD36, and 3 on both. The results indicated a significant association between UU colonization and BPD28 (odds ratio (OR): 2.26, 95% confidence interval (CI): 1.78-2.85, P < 0.00001, 23 studies, very low certainty of evidence) and BPD36 (OR: 2.13, 95% CI: 1.47-3.07, P < 0.0001, 16 studies, very low certainty of evidence). Conclusion: There is a correlation between UU colonization and the development of BPD in preterm infants. Future research should prioritize well-designed, large-scale, high-quality randomized controlled trials (RCTs) to comprehensively assess the risk of BPD in neonates following UU infection and to provide stronger evidence for clinical screening and prevention strategies to improve the prognosis of affected newborns.